The prefrontal cortex and neurological impairments of active thought. - Shallice, Tim.; Cipolotti, Lisa.
This article reviews the effects of lesions to the frontal cortex on the ability to carry out active thought, namely, to reason, think flexibly, produce strategies, and formulate and realize plans. We discuss how and why relevant neuropsychological studies should be carried out. The relationships between active thought and both intelligence and language are considered. The following basic processes necessary for effective active thought are reviewed: concentration, set switching, inhibiting potentiated responses, and monitoring and checking. Different forms of active thought are then addressed: abstraction, deduction, reasoning in well-structured and ill-structured problem spaces, novel strategy generation, and planning. We conclude that neuropsychological findings are valuable for providing information on systems rather than networks, especially information concerning prefrontal lateralization of function. We present a synthesis of the respective roles of the left and right lateral prefrontal cortex in active thought. -- (from the author)
Keywords: Active thought; Neuropsychology; Prefrontal cortex; Supervisory system; Reasoning; Lateralization of function